Stress and psychosomatic symptoms of primary school students - Vaselić, Nada V.; Mihajlović, Tatjana V. (Psihološka istraživanja, 2019)
Parents, school and teachers are the source of stress for students, and individual differences of students are reflected in terms of the perception of stress from the aforementioned sources. Stress may significantly contribute to psychosomatic symptoms. The objective of this research is to determine the relation between the perception of stress by parents, school and teachers, anxiety as a personality trait, and frequency and interference caused by psychosomatic symptoms. The sample includes 420 students of higher grades of primary school (46.9% of school girls) whose data were collected through Pen-and-Paper Technique. The following instruments were used in the research: The Scale of Intensity of School Stress for Students, Spielberger State-Trait Anxiety Inventory (STAI), as well as Psychosomatic Symptoms Questionnaire for Children and Adolescents. Research results indicate that the subscales of perception of stress are in statistically significant correlation with anxiety as personality trait (correlations range fromr=.26 tor=.29), as well as with frequency and interference caused by psychosomatic symptoms (correlations range from r=.17 tor=.21). The highest correlations were achieved between the anxiety as a personality trait and frequency of psychosomatic symptoms (r=.43) and this trait and interference caused by psychosomatic symptoms (r=.31). Anxiety is assumed as a mediating variable between perception of stress and frequency of psychosomatic symptoms, which is confirmed by the results (for subscale stress by the teacher: indirect effect –R2=.190, b=.513, SE=.127, p<.01; for subscale stress related to school: indirect effect –R2=.189, b=.607, SE=.128, p<.001). Research identified relation between perception of stress, anxiety and psychosomatic symptoms, indicating a need for education about the strategy for dealing with stress in the context of school.